2008
DOI: 10.1021/ol802479y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regioselective Hydroformylation of Styrene and Its Derivatives Catalyzed by Rh Complex with Tetraphosphorus Ligands

Abstract: Styrene has been hydroformylated to the linear aldehyde with surprisingly high regioselectivity (l/b up to 22 for styrene) by using Rh complex with tetraphosphorus ligand. To the best of our knowledge, this is the highest linear regioselectivity reported for the hydroformylation of styrene and its derivatives. This protocol is in sharp contrast to other processes that favor producing branched aldehyde (typically >95% branched for most bidentate systems).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 44 publications
2
36
0
1
Order By: Relevance
“…The electron-withdrawing properties of the pyrrolyl group give the ligand good p-accepting ability, which is favorable for linear aldehyde regioselectivity in either linear olefin or styrene hydroformylation. [9,17,22,23] Therefore, the relatively higher selectivity and activity caused by ligand 1 were attributed to the presence of electron-withdrawing pyrrolyl group. Analogously, it can be seen that ligand 4 containing the pyrrolyl group exhibited a higher L/B ratio than ligand 5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The electron-withdrawing properties of the pyrrolyl group give the ligand good p-accepting ability, which is favorable for linear aldehyde regioselectivity in either linear olefin or styrene hydroformylation. [9,17,22,23] Therefore, the relatively higher selectivity and activity caused by ligand 1 were attributed to the presence of electron-withdrawing pyrrolyl group. Analogously, it can be seen that ligand 4 containing the pyrrolyl group exhibited a higher L/B ratio than ligand 5.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al also revealed this phenomenon when they used ligand (III) in the Rh-catalyzed aryl alkene hydroformylation. [9] It is worth noting that the steric hindrance of the substrates remarkably influences the regioselectivity. [9] In our case, when a-methylstyrene was used as the substrate, few branched aldehydes were yielded (Table 3, entry 4), but the reaction rate decreased obviously.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1,4-addition of benzene derivatives to acrolein is a onestep aromatic substitution reaction to generate 3-arylpropanals as compared with the other routes, such as (a) oxidation of 3-arylpropan-1-ol, 10 (b) selective hydrogenation of cinnamyl aldehydes, 11 (c) hydroformylation of styrenes, 12 (d) arylation of allylic alcohols followed by isomerization, 13 and (e) hydrosilylation of cyclic malonates 14 (Scheme 1). The previous 1,4-addition of benzene derivatives to acrolein has been found only in the following three articles, indicating a limited substrate scope for the reaction: Alkyl-substituted benzenes, such as toluene, cumene, and tert-butylbenzene, added to acrolein using a stoichiometric amount of TiCl 4 , in up to a 38% yield (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%